(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the analgesic effect of shortwave therapy combined with electroacupuncture and acupressure massage in the treatment of mechanical low back pain. Subjects and methods: A prospective interventional clinical study with a before-and-after comparison design was conducted on 50 inpatients at the Department of Rehabilitation, Thanh Hoa Traditional Medicine and Pharmacy Hospital, who met the inclusion criteria. The treatment duration was 15 days, using a combination of shortwave therapy, electroacupuncture, and acupressure massage. The effectiveness was assessed based on pain level (VAS) and disability index (ODI). Results: After 15 days of treatment, both VAS and ODI scores significantly improved, with statistical significance (p < 0.05). Conclusion: The combination of shortwave therapy, electroacupuncture, and acupressure massage is effective in pain relief for patients with mechanical low back pain.